Size and thermal effects on sedimentation behaviors of two spheres - Yang, Bo; Chen, Sheng; Xiong, Yan; Zhang, Rui; Zheng, Chuguang (Elsevier, 2017)
Gas-solid flows are commonly found in nature, as well as in industries. In such flows the size of the solid particles generally is not uniform. In addition, usually there is heat transfer between solid particles and gas flows. The hydrodynamics and heat transfer both make the behavior of gas-solid flows extremely complicated. In order to reveal these effects, in this paper three cases: (1) two isothermal, (2) two hot and (3) two cold spherical particles with various size ratios are investigated using lattice Boltzmann method-immersed boundary (LB-IB). It is observed that, for the first time, the tumbling duration of both two hot particles and two cold particles settling in vertical channel, is prolonged with size ratio increasing. The differences of threshold size ratio among the three cases are significant and the threshold size ratio of two hot particles is the largest one. Especially, it is found that heat transfer affects critically the interaction of two hot particles with low size ratios. In addition, against particle size ratio increasing, heat transfer effects on the interaction between two non-identical particles become weak.